Glycopolymer monoliths for affinity bioseparation of proteins in a continuous-flow system: glycomonoliths. Issue 6 (13th January 2017) - Seto, Hirokazu; Shibuya, Makoto; Matsumoto, Hikaru; Hoshino, Yu; Miura, Yoshiko
Abstract : Macroporous materials, called glycomonoliths, were prepared from saccharide-containing monomers, and applied for affinity bioseparation of proteins in a continuous-flow system. Abstract : In this study, macroporous materials, called glycomonoliths, were produced from saccharide-containing monomers, and used for affinity bioseparation of proteins in a continuous-flow system. The porous structure formation of the glycomonoliths involved polymerization-induced phase separation of the polyacrylamide unit. The pore size could be controlled between several hundred nanometers and several micrometers by changing the alcohol used as the porogenic solvent during the preparation of the monolith. The glycomonolith pores allowed for the permeation of solutions through the monoliths, which meant that they could be used in a continuous-flow system. The adsorption capacities of the glycomonoliths for the saccharide-binding protein (concanavalin A) were larger than that of a glycopolymer-grafted material because of the higher saccharide densities in the monoliths than the grafted material. When concanavalin A was eluted from the glycomonolith, the concentration of concanavalin A in the effluent was up to 11 times higher than that in the feed solution. The adsorption of concanavalin A to the glycomonolith was specific, even in the presence of other proteins.